2017
DOI: 10.1016/j.euroneuro.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of agomelatine (10 or 25 mg/day) in non-depressed out-patients with generalized anxiety disorder: A 12-week, double-blind, placebo-controlled study

Abstract: Agomelatine is efficacious in reducing symptoms and preventing relapse in placebo-controlled trials in generalised anxiety disorder (GAD). Nevertheless, fixed dose studies of agomelatine in GAD have not been undertaken. To determine the minimally effective optimal dose of agomelatine in GAD, the efficacy of two doses of agomelatine (10 and 25mg/day) was investigated in a 12-week, placebo-controlled, double-blind, international study in patients with a primary diagnosis of GAD. The primary outcome measure was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Furthermore, the combined treatment of ineffective doses of melatonin and diazepam has been reported to show an anxiolytic-like effect [ 55 ]. In recent human studies, agomelatine, a melatonergic receptor agonist, was effective in the treatment of generalized anxiety disorder [ 56 , 57 ]. The agomelatine also demonstrated efficacy in the treatment of panic disorder [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the combined treatment of ineffective doses of melatonin and diazepam has been reported to show an anxiolytic-like effect [ 55 ]. In recent human studies, agomelatine, a melatonergic receptor agonist, was effective in the treatment of generalized anxiety disorder [ 56 , 57 ]. The agomelatine also demonstrated efficacy in the treatment of panic disorder [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antidepressant agomelatine-which acts as an agonist for melatonin MT 1 and MT 2 receptors and as an antagonist for serotonin 5-HT 2C receptors-was shown to be effective in four studies in GAD. [55][56][57][58] However, the drug is only licensed for the treatment of major depression, not for GAD. With agomelatine, discontinuation symptoms 59,60 and sexual dysfunction 61 are less likely than with SSRI or SNRI antidepressants.…”
Section: Agomelatinementioning
confidence: 99%
“…All studies were multi-centered, multinational trials conducted outside of US. Three were short-term clinical trials with 12 weeks of study duration [ 17 , 28 , 29 ]. One trial involved a 26-week double-blinded, placebo-controlled trial in GAD patients who showed optimal remission with agomelatine [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used identical dose of agomelatine, 25−50 mg/day [ 17 , 18 , 28 ]. However, in one study, the agomelatine group was further randomized into agomelatine 10 mg/day or 25 mg/day [ 29 ].…”
Section: Resultsmentioning
confidence: 99%